Evaluasi dan Perbaikan Desain Antar Muka Pengguna Situs Talangin.com Menggunakan Pendekatan Human Centered Design (HCD) - Natasha Syahirsah; Ismiarta Aknuranda; Himawat Aryadita (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Talangin.com is an organization engaged in the field of financial technology that utilizes the website as the main window for purchases made between buyers and sellers from other e-commerce. How to do business on Talangin website is the use of funds made by Talangin which will be discarded by the buyer to the gutters in the form of repayments. Talangin is still in the development stage is currently more focused on the use of PHP and not focusing to usability. In addition, there is still an answer in the interaction of users and systems that exist on Talangin sites from the suitability of their interaction with Islamic Shari'a. Based on the poverty, then at this time carried out the evaluation and design website Talangin using Human Centered Design approach (HCD). HCD is a method that involves humans in the process of designing. The research phase is to determine the use, determine the user, dig the design, and anticipate the design. The results of this study are evaluations and designs that have been evaluated with the Focus Group Discussion (FGD) approach and afterwards confirmed with the Talangin, based on the results of the research that have been in accordance with the usefulness and in accordance with Islamic Shari'a.